Knowledge Upgrade to Wisdom by Using Knowledge Broker Agent for Web Application, Based on Users’ Experiences - Abdullah, Hasanen S; Ali, Roaad A (Al-Nahrain Journal of Science, 2017)
Knowledge is an important factor in conduct individual’s life and decision-making process, so decision’s efficiency and power is dependent on knowledge deepen which is possess by individual. The aim of this paper is to build an improved intelligent web application system to provide web service which upgrades and raises knowledge level to wisdom level by aggregate knowledge with experience. The web service is implemented by using the brokerage approach through agent-based knowledge broker web service system, and it related to pre-define field. Java Agent DEvelopment (JADE) platform is used in this system to provide the demand environment for knowledge broker agent to achieve its behaviors. Practical testing by submitting different query belong to the medical field (radiography) demonstrate the system efficiency in retrieving knowledge relevant to submitted query and provide level of knowledge upgraded to wisdom to sustain and support specialist users’ capabilities in making decisions reach wise decisions level.